Gender and activity disparities in the relationship between circadian syndrome and gallstone disease - Binbin Feng; Tianlin Wang; Junquan Han; Zhaoshuai Yang; Hong Wang; Huizhen Li (Frontiers in Endocrinology)
ObjectiveTo explore the potential correlation between gallstone disease (GSD) prevalence and circadian syndrome (CircS).MethodsThe cross-sectional research utilized data spanning 2017 to March 2020, sourced from the National Health and Nutrition Examination Survey (NHANES). The GSD data were collected via questionnaires, with appropriate sample weights applied to ensure the study population was representative. Three multivariable logistic regression models were built to clarify the connection between CircS and GSD. Furthermore, subgroup analysis and interaction test were carried out, categorized based on demographic traits and lifestyle aspects, to discern the potential influence of these variables on the correlation.ResultsThe analysis included 4,126 participants, with a prevalence of 38.68% for CircS and 12.04% for GSD. The multivariable logistic regression analysis indicated a positive correlation between CircS and the prevalence of GSD (Odds Ratio (OR) = 1.336, 95% Confidence Interval (CI): 1.048, 1.702). When stratified by the number of CircS components, a positive correlation was observed between the number of CircS components and the prevalence of GSD (P for trend < 0.05). In particular, individuals with six or more CircS components had a higher prevalence of GSD than those with three or fewer components (OR = 2.608, 95% CI: 1.464, 4.647). The subgroup analysis and interaction test revealed that a positive correlation between CircS and GSD prevalence was mainly observed in female individuals (OR = 1.701, 95% CI: 1.236, 2.341) and individuals not engaged in moderate activity (OR = 1.990, 95% CI: 1.158, 3.418).ConclusionThere is a positive correlation between CircS and GSD prevalence, particularly among females and individuals not engaging in moderate activity. These findings offer new insights for research directions in GSD and may impact preventive and therapeutic strategies.